Psychometric Testing of the Japanese Version of the Daily Record of Severity of Problems Among Japanese Women - Takeda T; Kai S; Yoshimi K (Dove Medical Press, 2021)
Takashi Takeda,1 Sayaka Kai,1,2 Kana Yoshimi1 1Division of Women’s Health, Research Institute of Traditional Asian Medicine, Kindai University, Osaka-Sayama, Osaka, 589-8511, Japan; 2Department of Obstetrics and Gynecology, Kindai University Faculty of Medicine, Osaka-Sayama, Osaka, 589-8511, JapanCorrespondence: Takashi TakedaDivision of Women’s Health, Research Institute of Traditional Asian Medicine, Kindai University, 377-2 Ohno-Higashi, Osaka-Sayama, Osaka, 589-8511, JapanTel +81-72-366-0221 (Ext. 3393)Fax +81-72-366-6661Email take@med.kindai.ac.jpPurpose: The Daily Record of Severity of Problems (DRSP) is commonly used to assess premenstrual syndrome and premenstrual dysphoric disorder throughout the world. The aim of this study was to assess the validity and reliability of the Japanese version of the DRSP (DRSP-J).Materials and Methods: We analyzed 324 women with regular menstrual cycles who completed the DRSP-J and the Premenstrual Symptoms Questionnaire (PSQ). They had all applied to participate in an ongoing study for the treatment of their premenstrual symptoms. The DRSP-J was examined for evidence of reliability and validity. To examine reliability, we assessed Cronbach’s α, a measure of internal consistency, and test–retest reliability. We assessed structural validity with principal component factor analysis (PCA) and confirmatory factor analysis (CFA). We used PSQ total score to examine concurrent validity.Results: Cronbach’s α for DRSP total score was 0.97. DRSP total score and individual items showed high test–retest reliability. PCA showed a two-factor model describing mood and behavioral and physical symptoms. CFA showed that the two-factor model derived from the PCA was an acceptably good fit. DRSP total score correlated moderately with PSQ total score (r = 0.42).Conclusion: The DRSP-J showed reliable and valid measures of premenstrual symptoms in Japanese women.Keywords: premenstrual syndrome, premenstrual disorders, psychometric testing, validity